Nutritional and Gastroenterological Monitoring of Patients With Celiac Disease During COVID-19 Pandemic: The Emerging Role of Telemedicine and Point-of-Care Gluten Detection Tests - Costantino, Andrea; Roncoroni, Leda; Noviello, Daniele; Nandi, Nicoletta; Lombardo, Vincenza; Scricciolo, Alice; Scaramella, Lucia; Vecchi, Maurizio; Elli, Luca (Frontiers in Nutrition, 2021)
Background and Aim: Since the beginning of the COVID-19 pandemic, telemedicine has been supporting many patients with chronic diseases worldwide. However, data on celiac disease (CeD) nutritional and gastroenterological remote monitoring are scanty. The aim of our study was to verify patients’ trust in telemedicine and to evaluate feasibility of telemedicine in dietetic monitoring. Material and Methods: We used telemedicine in place of the scheduled but not provided follow-up visits during the first lockdown of the COVID-19 pandemic. Patients received a phone call, and televisits were conducted for CeD patients with mild or moderate symptoms and/or with blood alterations. The patient’s adherence to the Gluten Free Diet (GFD) was evaluated according to the Celiac Dietary Adherence Test (CDAT). When gluten contamination was suspected, a point-of-care gluten detection test was prescribed. The patient’s trust in telemedicine was assessed, through an adapted version of the Patient Trust Assessment Tool (PATAT) questionnaire, as the percentage of patients giving a score of at least 4 out of 5 on a Likert Scale for 3 selected key statements: “I can trust televisit”, “I can trust that possible problems with the telemedicine service will be solved properly” and “I feel at ease when working with this website”. Results: One-hundred-twelve CeD patients were phone called; among symptomatic patients, 39 out of the 42 scheduled (92.9%) televisits were performed. Among the 39 visits, 34 (87.2%) questionnaires were compiled. The patients included in the study obtained a CDAT score from 7 to 13 (11±2). Gluten detection tests were prescribed to eleven patients, resulting positive in 2. Trust in the telemedicine service was achieved in 94.1%, 88.2% and 97.1% for the three selected key statements of the PATAT questionnaire. Conclusion: During the COVID-19 pandemic, telemedicine showed to be feasible and the majority of patients trusted the combined gastroenterological and nutritional televisits. Gluten detection tests demonstrated to be useful tools for the patient and for the caregiver to confirm the adherence to the GFD remotely.